Burning velocity and Markstein length blending laws for methane/air and hydrogen/air blends. (1st January 2017) - Bradley, D.; Lawes, M.; Mumby, R.
Abstract: Because of the contrasting chemical kinetics of methane and hydrogen combustion, the development of blending laws for laminar burning velocity, ul, and Markstein length for constituent mixtures of CH4 /air and H2 /air presents a formidable challenge. Guidance is sought through a study of analytical expressions for laminar burning velocity. For the prediction of burning velocities of blends, six blending laws were scrutinised. The predictions were compared with the measured burning velocities made by Hu et al. under atmospheric conditions[1] . These covered equivalence ratios ranging from 0.6 to 1.3, and the full fuel range for H2 addition to CH4 . This enabled assessments to be made of the predictive accuracy of the six laws. The most successful law is one developed in the course of the present study, involving the mass fraction weighting of the product of ul, density, heat of reaction and specific heat, divided by the thermal conductivity of the mixture. There was less success from attempts to obtain a comparably successful blending law for the flame speed Markstein length, Lb, despite scrutiny of several possibilities. Details are given of two possible approaches, one based on the fractional mole concentration of the deficient reactant. A satisfactory empirical law employs mass fraction weighting of the product ul Lb .